Linkages Between Macroeconomic Variables and the BSE Stock Indices :An Application of the Vector Error Correction Model - Shah, Preksha (2007)
The research analyses relationships among macroeconomic variables and BSE Stock Indices from April, 1999 to March, 2007. By employing the Johansen's Vector Error Correction Model, results indicate that the impact of macroeconomic variables on the fundamental indices and sectoral indices vary, necessitating the requirement for separate sectoral studies. While industrial production is found to drive the BSE capital goods index in the long run, it is negatively related to the BSE consumer durables index. The exchange rates seem to affect the BSE capital goods index in the long run but not BSE consumer durables index. The nature of the relationship between the call rates and the two indices is also opposite in the long run. In the short run also, the responses of both the indices to the call as well as the exchange rate are in opposite directions.